Comparison of Effect of Sub-Tenon’s and Peribulbar Local Anesthesia on Intraocular Pressure (IOP) for Cataract Surgery - Ayesha Chandni, Shahid Mahmood Dayal, Daniyal Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: to determine the change in intraocular pressure after sub-Tenon’s vs peribulbar local anesthesia in patients undergoing cataract surgery. Study Design: Randomized controlled trial Place and Duration of Study: Department of Ophthalmology, Allama Iqbal Memorial Teaching Hospital, Sialkot from 28th December 2020 to 27th June 2021 Methodology: Total 60 patients (30 in each group) were enrolled in the study. Patients were divided randomly into 2 groups by method of lottery. In group A, sub-Tenon’s anesthesia was used, and in group B, peribulbar anesthesia was used.Digital pressure was started after administration of anesthesia and continued for ten minutes with 10 seconds interval after every two minutes. Results: In this study there were 33(55%) were male and 27(45%) were females.At baseline the mean IOP of the patients with peribulbar anesthesia was 14.83±2.00 mmHg while in patients with sub-Tenon’s anesthesia it was 14.27±1.59 mmHg (p-value =0.230). after 1 minute mean IOP of patients with peribulbar anesthesia was 23.10±4.39 mmHg while in patients with sub-Tenon’ s anesthesia, it was 18.50±1.94 mmHg (p<0.001). after 15 minutes mean IOP was 19.53±3.02 mmHg in patients with peribulbar anesthesia and 15.57±1.35 mmHg in patients with sub-Tenon’s anesthesia (p<0.001). Conclusion: This study concluded that there is significantly more mean change in IOP with peribulbar anesthesia noted as compared to sub-Tenon’sanesthesia for cataract surgery. Keywords: Cataract surgery, sub-Tenon’s anesthesia, peribulbar anesthesia.